Quel(s) sens pour les structures du type ? (avec application à un corpus de nouvelles de Steven Millhauser) - Catherine DELESSE (E-REA)
This article aims at studying verbs of reporting and opinion which can be used in the passive with two different structures : one with subject raising , the other with extraposition of a that-clause . The characteristics of those verbs, both syntactic and semantic, are described, as well as a brief summary of historical data. Then the study focuses on the use of both structures in a corpus of short stories by Steven Millhauser who uses them in an interesting way.